A 1992 social accounting matrix (SAM) for Tanzania - Wobst, Peter (International Food Policy Research Institute, 1998)
As part of the Tanzania country study being done under the IFPRI research project on Macroeconomic Reform and Regional Integration in Southern Africa (MERRISA), a social accounting matrix (SAM) has been constructed for the base year 1992. A SAM is a square matrix consisting of row and column accounts that represent the different sectors, agents, and institutions of an economy at the desired level of disaggregation. The SAM, a useful framework for consistent multi-sectoral economic data preparation, represents the expenditure-receipt flows among all actors and sectors of the entire economy, capturing both input-output and national income and product data. Because the analytical focus of the MERRISA project is agriculture and because agricultural production in Tanzania accounts for about half of GDP, the disaggregated Tanzania SAM contains 21 agricultural sectors out of 56 sectors in total. The Tanzania SAM consists of 56 activity accounts capturing the flows belonging to the domestic production process and 55 commodity accounts capturing the flows belonging to the marketing process of nationally and internationally produced goods. The factor disaggregation of productive factors consists of Capital, Land and 5 labor categories, while households are divided into Rural Farmers, Rural Non-Farmers, Urban Farmers, and Urban Non-Farmers.